Light‐controlled smart materials: Supramolecular regulation and applications - Zi‐Hao Liao; Feng Wang (Smart Molecules)
Abstract Smart materials serve as the fundamental cornerstone supporting humanity's transition into the intelligent era. Smart materials possess the capability to perceive external stimuli and respond accordingly. Light‐controlled smart materials (LCSMs) are a significant category that can sense and respond to light stimuli. Light, being a non‐invasive, precisely regulated, and remotely controllable source of physical stimulation, makes LCSMs indispensable in certain application scenarios. Recently, the construction of LCSMs using supramolecular strategies has emerged as a significant research focus. Supramolecular assembly, based on non‐covalent bonding, offers dynamic, reversible, and biomimetic properties. By integrating supramolecular systems with photoresponsive molecular building blocks, these materials can achieve synergistic and rich intelligent stimulus responses. This review delves into the latest research advancements in LCSMs based on supramolecular strategies. There are four sections in this review. The first section defines LCSMs and outlines their advantages. The second section discusses the design approaches of supramolecular LCSMs. The third section highlights the latest advancements on supramolecular LCSMs over the past 3 years. The fourth section summarizes the current research and provides insights into the future development of this field.